MPC-11 Comprehensive gene expression analysis of IDH-mutated astrocytomas with 19q-loss. (28th November 2020) - Otani, Ryohei; Mukasa, Akitake; Uzuka, Takeo; Higuchi, Fumi; Matsuda, Hadzki; Tanaka, Shota; Kim, Phyo; Ueki, Keisuke
Abstract: We previously reported that there was a subgroup of IDH-mutated astrocytomas harboring only 19q-loss showing oligodendroglioma-like morphology and significantly longer overall survival (OS) compared with 19q-intact astrocytomas. To further explore the biological characteristics of this possible subgroup and obtain insight into the mechanism of their relatively benign clinical behavior, we compared gene expression pattern between five 19q-loss and five 19q-intact IDH-mutated astrocytomas by microarray analysis. By comparing expression levels of genes of 19q-loss astrocytomas to those of 19q-intact astrocytomas, 136 up-regulated genes and 203 down-regulated genes were extracted. Down-regulated genes in the 19q-loss astrocytomas were heavily clustered to 19q and 4p, and up-regulated genes to 4q. It was noted that fibroblast growth factor 1 associated with stem cell maintenance was down-regulated in 19q-loss astrocytomas and genes associated with glioma progression were differentially expressed, these results were validated with the independent TCGA data set. On t-SNE analysis of the 19q-loss astrocytomas with other IDH-mutant glioma subgroups from the TCGA datasets, 19q-loss astrocytomas did not shift to oligodendrogliomas with 1p/19q codeletion but were a subgroup in astrocytomas. These results indicated that 19q-loss in astrocytomas is more likely to be an acquired event rather than early event in oncogenesis like 1p/19q codeletion in oligodendrogliomas, and the biological and morphological features of 19q-loss astrocytomas were possibly related to differentially expressed genes associated with stem cell maintenance and glioma progression.